Factors Associated with Increased Risk of Recurrence following Treatment of Trigger Finger with Corticosteroid Injection - Flensted, Frederik; Jensen, Claus Hjorth; Daugaard, Henrik; Vedel, Jens-Christian; Jørgensen, Rasmus Wejnold (Journal of Hand and Microsurgery, 2020)
Introduction  The aim of the study was to estimate recurrence rates, time to recurrence, and predisposing factors for recurrence of trigger finger when treated with corticosteroid (CS) injection as primary treatment.Materials and Methods In a retrospective chart review, we identified primary trigger fingers treated with CS injection as primary treatment. Affected hand and finger, recurrence, time to recurrence, duration of symptoms, secondary treatment type, and comorbidities were recorded. A total of 539 patients were included with a mean follow-up of 47.6 monthsResults In total, 330/539 (61%) recurrences were registered. Mean time to recurrence was 312 days. Increased risk of recurrence was seen after treatment of the third finger (relative risk [RR]: 1.22; 95% confidence interval [CI]: 1.06–1.39). Several comorbidities were associated with increased risk of recurrence: carpal tunnel syndrome (RR: 1.27; 95% CI: 1.07–1.52), thyroid disease (RR: 1.45; 95% CI: 1.15–1.83), or shoulder diseases (RR: 1.58; 95% CI: 1.36–1.83).Conclusion We found a recurrence rate after primary treatment of CS injection for trigger finger of 61%. Most recurrences happened within 2 years and we found treatment of third finger, carpal tunnel syndrome, shoulder, or thyroid disease to be associated with an increased risk of recurrence of symptoms.
Keywords: trigger finger; recurrence; primary treatment; cofactors